Amazon and Petén: Two Regions Unsuitable for the Development of Civilization? - Solórzano Fonseca, Juan Carlos (2018)
For most of the Twentieth century archeologists and ethnologists agreed to think that regions such as the Amazon in Brazil, Peten forest in Guatemala, Belice and southern Yucatan were areas where agricultural systems able to support large population centers with complex societies were not possible at pre-Columbian times. Their type of soils, vegetation and climate made this step in civilization almost unattainable. However, new findings and studies at the end of last century challenged this idea. New data and close examinations of old chronicles from Sixteenth and Seventeenth centuries probe that autochthonous populations inhabiting the Amazon as well as Peten forest managed to develop sophisticated and productive farming systems. These techniques could not only feed large populations but made also possible the rise of complex societies.